PENERAPAN METODE MIND MAPPING TERHADAP PEMBELAJARAN MENULIS TEKS ANEKDOT PADA SISWA SMK - Lina Prastiawati; Erlin Erliana; Indra Permana (IKIP Siliwangi, 2019)
This research was motivated by the existence of data from the observations in the form of evaluation data of Vocational School students, amounting to 20 students experiencing difficulties in learning to write anecdotal texts because the teacher did not involve students so students were less active and not motivated to learn. The study was made aimed at overcoming the problem, researchers used the mind mapping method in the hope of increasing the ability of students in learning to write anecdotal texts. This study uses a quasi-experimental design by designing a comparison of control group design with pretest-posttest data collection techniques. Based on the research the results of the average pretest score were 74.45 and posttest was 80.95. So the conclusion is that the application of mind mapping methods is very effectively applied in learning to write anecdotal texts because of the results of the comparison which shows an increase in value.